Air Pollutants Causing Diseases, Their Detection and Measurement Using Different Hyphenated Analytical Techniques: A Quick Insight - Bairagee, Deepika (Asian Journal of Pharmaceutics (AJP), 2023)
Air pollution, a significant environmental risk factor, is regarded to be the root cause of certain ailments, including asthma, lung cancer, and ventricular hypertrophy. According to the World Health Organization, some of the major air pollutants include lead, carbon monoxide (CO), sulfur oxides, CO at ground level, and particle pollution. Both short-term and long-term exposure to polluted air can have a number of toxicological consequences on the human body, including respiratory and cardiovascular problems, neuropsychiatric issues, eye irritation, skin conditions, and chronic illnesses like cancer. Different advanced analytical techniques such as gas chromatography-mass spectrometry, infrared radiation absorption, and laser, where laser radiation is sent through a sample of atmosphere to be investigated either as transmission, or the scattering of the light all the way through a different physical process, produce a variety of different techniques for monitoring air quality. This article has detailed the primary air pollutants, their sources of emission, their effects on human health, and the methods used to detect them to discover solutions to minimize them.